Pengaruh Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Biaya Operasional Dan Pendapatan Operasional (BOPO) Terhadap Profitabilitas BPR - Yunus Fiscal; Lili Lusiana (Jurnal Akuntansi dan Keuangan, 2014)
This research aims to know the influence of variable CAR, LDR, BOPO and against the BPR diproksikan Profitability with ROA. The Data used in this study were obtained from the publication of the annual financial statements of the respective website of BPR in 2010-2012. The number of samples as many as 12 recorded on BPR Bank Indonesia with the period of 2010-2012 in the province of Lampung were taken through purposive sampling. Analytical techniques used was multiple linear regression analysis. The results showed that the variable CAR and LDR have no effect against ROA. While variables affect the BOPO ROA. The ability of a third independent variable predictive of ROA is 81.2% of the indicated size adjusted R2 equal to 18.8%, the rest is explained by other variables outside of a research model.